Originally Posted by

**ella85** All that you've done so far is correct.

You need to sub y = 3/x into either of the original equations, so you will get

x^2 * 3/x = 1 Mr F says: What equation have you used here?

or x^2 + 9/x^2 = 10

the first equation is probably simpler Mr F says: The first equation is xy = 3 => y = 3/x. Which is where the OP got y = 3/x from in the first place.

you then simplify it to get 3x^2/x = 3 Mr F says: The first equation is NOT x^2 y = 3 .....

then multiply both sides by x so that

3x^2=3x

and so you can see that x = 1

i hope that helped=]